2012
DOI: 10.1097/acm.0b013e31825373b3
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention to Improve Cost-Effective Care Among Medicine Housestaff

Abstract: A brief intervention featuring a discussion of hospital bills can fill a gap in resident education and reduce laboratory costs for a subset of patients, but may increase readmission risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…This has led to the development of multiple educational curricula 10 25 26. Several prior studies have demonstrated the immediate impact of didactic or audit-and-feedback interventions on physicians’ cost knowledge or ordering behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the development of multiple educational curricula 10 25 26. Several prior studies have demonstrated the immediate impact of didactic or audit-and-feedback interventions on physicians’ cost knowledge or ordering behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective review of cost information, however, may not be effective at achieving real cost savings. 19 In addition, that methodology does not guide residents toward the practice of evidence-based medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that this was a small, single-institution sample of medical students near the beginning of their clinical training, students were able to identify many common practices, echoed by residents [ 2 ] and attendings [ 3 ], that were not consistent with the practice of high-value care. However, the possibility for availability bias is pronounced, as the themes outlined by students closely mirrored those taught in the required online module.…”
mentioning
confidence: 94%